Evaluation of captopril and nefediplne in Treatment of hypertension secondary to Post streptococcal acute Glomerulonephritis - A randomized control trial - Azim, Aznor Fadly (2012)
Post-streptococcal Acute Glomerulonephritis (PSAGN) is still common in Malaysia. Hypertension is one of its main complications which can lead to severe morbidity in children. Conventional method in treating hypertension in these patients was to use nifedipine to reduce the blood pressure. Recent study in the pathophysiology of the disease had shown apart from water and sodium retention, inappropriate production of angiotensin II could also contributes to the development of hypertension. Captopril, an angiotensin converting enzyme inhibitor can help to reduce the production of angiotensin II which can cause blood pressure reduction. To compare the effectiveness of captopril versus nifedipine in controlling blood pressure in children with PSAGN with hypertension. This was a double blinded randomized controlled trial, registered with ANZCTR (Trial No: ACTRN12611000778987) All children admitted to Wad 6 Selatan HUSM diagnosed clinically with PSAGN with hypertension during a one year study period are eligible for the study. Subjects were randomized either to receive nifedipine (control) or captopril (intervention). Outcomes measured are blood pressure changed in the first 4 hours and blood pressure changes until Day 3 of starting the medication, duration of days to achieve blood pressure control, total duration of admission and the need to use additional medication. Blood urea and serum creatinine levels are compared from before starting treatment and at Day 3 after starting treatment. Out of 40 patients who were recruited and randomized, only 19 from the nifedipine treatment group and 13 from the captopril treatment group completed the study. Both treatment groups had no difference in their baseline data. Nifedipine produces a more significant reduction in SBP and DBP compared to captopril in the first 4 hours of starting treatment (SBP p= 0.001, DBP — 0.016). There was no difference in reduction of SBP and DBP after 8 hours of treatment between the groups (SBP p=0.630, DBP p=0.497). There were no significant differences in the duration of blood pressure normalization (nifedipine: 2.7 days, captopril 2.9 days, p= 0.803) and duration of admission (nifedipine: 6.9 days, captopril: 5.4 days; p=0.183) and the need for additional medication to control the blood pressure (p=0.32) between the groups. Changes of blood urea and serum creatinine levels were not significant before and after treatment (Blood urea changes, /?= 0.564; serum creatinine changes, p- 0.236). Nifedipine produces more significant blood pressure reduction in SBP and DBP in the first 4 hours of starting treatment.